Carbon Stock of Different Parts of Major Plant Species of Three Ecological Zones of Bangladesh Sundarbans (Bangladesh Journal of Botany, 2021)
The biomass and carbon sequestration by different parts namely leaf, stem and roots of major dominant plant species of different quadrats established in three ecological zones of Bangladesh Sundarban Mangrove Forests (SMF) were determined. A visit was done during 28 March to 1 April 2016 covering the oligohaline, mesohaline and polyhaline zones of SMF. Plant parts (stem, branch and leaf) of major plant species were collected from 16 quadrats of different locations. The major plant species were selected on the basis of abundance (number). Aboveground biomass (AGB) was estimated as the product of tree volume and wood density. Below ground biomass (BGB) were estimated from the 20% of above ground stem biomass. Carbon stock and CO2 sequestration were estimated from the dry weight of AGB and BGB. A total of 20 species in 16 different quadrats in three ecological zones and overall SMF was recorded. Among 20 species 10 dominant tree species were considered on the basis of abundance (number) for the estimation of AGB, BGB and CO2 sequestration. Species wise mean AGB (ton/ha) of 10 dominant mangrove trees are in order Heritiera fomes (186.423) > Excoecaria agallocha (28.752) > Avicennia officinalis (24.082) > Ceriops decandra (5.021) > Cynometra ramiflora (1.403) > Tamarix dioica (0.592) > Xylocarpus moluccensis (0.500) > Bruguiera gymnorrhiza (0.307) > Aegiceras corniculata (0.241) > Aglaia cuculata (0.038).Species wise mean BGB (ton/ha) of 10 dominant mangrove trees are in order H. fomes (34.99) > E. agallocha (4.94) > A. officinalis (4.79) > C. decandra (0.704) > X. moluccensis (0.47) > C. ramiflora (0.15) > B. gymnorrhiza (0.018) > A. corniculata (0.015) > T. dioica (0.008) >A. cuculata (0.004). The total CO2 sequestered (above ground and below ground) in overall SMF (considered land area 4143 km2) was 192.869 megaton.Bangladesh J. Bot. 50(2): 373-385, 2021 (June)